Mind Set of Indian Accounting Professionals and Environmental Accounting - L. Augustin Amaladas; M. Nirmala (European Scientific Journal, ESJ, 2017)
Those who do not plan, cannot control and it is difficult for them to control if they do not have an accurate measurement. Those who do not measure cannot report. If not reported, the regulating authorities and governments will not have an effective control on pollution to fulfill the global requirements. The mindset of financial accounting professionals who prepare financial accounts and reporting to shareholders and management is positive which would help the Government of India for the implementation of environmental accounting and reporting to the stake holders. Structured questionnaire were used and collected as primary data. The accounting professionals were in the opinion that reporting on environment related issues of the company would give positive impact on the Indian companies.